What Kind of Movement is Black Lives Matter? The View from Twitter. (September 2019) - Tillery, Alvin B.
Abstract: This paper examines the ways that social movement organizations affiliated with the Black Lives Matter (BLM) movement use Twitter through three content analysis studies. The main finding presented in the paper is that the modal tweet generated between December 1, 2015 and October 31, 2016 was an emotional response—an expression of sadness, outrage, or despair—to police brutality and the killings of African Americans. The second key finding is that BLM organizations generated more tweets that framed the movement as a struggle for individual rights than ones that utilized frames about gender, racial, and LGBTQ identities. Finally, the paper shows that BLM activists urge their followers to pursue disruptive repertoires of contention less frequently than they encourage other political behaviors. These findings suggest that the BLM movement is intelligible through both the resource mobilization and new social movement paradigms within social movement studies.